2018
DOI: 10.3390/app9010028
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Moment Redistribution in Statically Indeterminate Reinforced Concrete Structures Using Artificial Neural Network and Support Vector Regression

Abstract: In this paper, a new prediction model is proposed that fully considers the various parameters influencing the moment redistribution in statically indeterminate reinforced concrete (RC) structures by using the artificial neural network (ANN) and support vector regression (SVR). Twenty-four continuous RC beams and 12 continuous RC frames with various design parameters were tested to investigate the process of moment redistribution. Based on the experimental results obtained from this study and the published lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…ANN has been the most popular (thirty-five studies) in the construction/building materials field, while ANFIS and SVM were used by five, and FL and MGGP by four studies. In terms of the sub-disciplines where the AI tools were used, the list comprises a wide range of topics, such as predicting compressive strength of concrete (Pham et al , 2019; Dutta et al , 2018; Tanyildizi, 2018; Liu and Zheng, 2019; Ghanizadeh and Rahrovan, 2019; Al-Gburi et al , 2018; Sadowski et al , 2018; Gazder et al , 2017; Reddy, 2018; Behnood and Golafshani, 2018; Nguyen et al , 2019), measuring the adhesion/cohesion force between asphalt molecules at nanoscale level (Hassan et al , 2018), estimating the shear strength from the relative density, particle size, distribution (gradation), material hardness, gradation and fineness modulus (Yang et al , 2019; Li et al , 2019), confining (normal) stress, forecasting atmospheric corrosion of metallic materials (Zhu et al , 2019) and modelling the surface roughness in the turning of hardened AISI H11 steel (Saini et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…ANN has been the most popular (thirty-five studies) in the construction/building materials field, while ANFIS and SVM were used by five, and FL and MGGP by four studies. In terms of the sub-disciplines where the AI tools were used, the list comprises a wide range of topics, such as predicting compressive strength of concrete (Pham et al , 2019; Dutta et al , 2018; Tanyildizi, 2018; Liu and Zheng, 2019; Ghanizadeh and Rahrovan, 2019; Al-Gburi et al , 2018; Sadowski et al , 2018; Gazder et al , 2017; Reddy, 2018; Behnood and Golafshani, 2018; Nguyen et al , 2019), measuring the adhesion/cohesion force between asphalt molecules at nanoscale level (Hassan et al , 2018), estimating the shear strength from the relative density, particle size, distribution (gradation), material hardness, gradation and fineness modulus (Yang et al , 2019; Li et al , 2019), confining (normal) stress, forecasting atmospheric corrosion of metallic materials (Zhu et al , 2019) and modelling the surface roughness in the turning of hardened AISI H11 steel (Saini et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the comparative analysis of the results of calculations of reinforced-concrete statically determinable beams obtained according to the techniques of construction norms and, as a result, of applying the trained ANN with verification according to the data of samples of reinforced-concrete structures has shown that the results obtained with the use of the ANN have higher accuracy [2]. When evaluating the results of tests of reinforced-concrete frames, the accuracy is even higher in comparison with that provided in the design standards: the error when using the ANN is 6.8% versus 30-64% provided in various national design standards [3].…”
Section: Ann In the Problems Of Calculation Of Structural Unitsmentioning
confidence: 98%
“…. SVM is a learning method to define a hyperplane for data classification and regression [18,[40][41][42]. In the regression case, the goal of the SVM is to define the hyperplane close to as many of the data points as possible [40].…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%